Comparative studies of loblolly pine biodegradation and enzyme production by Argentinean white rot fungi focused on biopulping processes - Levin, Laura Noemí; Villalba, Laura; Da Re, Cristina Verónica; Forchiassin, Flavia; Papinutti, Víctor Leandro (Process Biochemistry)
The ability of eight white rot fungi: Coriolopsis rigida, Coriolus versicolor var. antarcticus, Peniophora sp., Phanerochaete sordida, Pycnoporus sanguineus, Steccherinum sp., Trametes elegans and Trametes villosa to selectively delignify loblolly pine (Pinus taeda) chips was studied. They were selected among 34 basidiomycetes from Argentina because of their capacity to decolorize Poly R-478 and Azure B. Fungal pretreatment caused changes in wood chemical composition as well as in physical structure. The present study allowed the identification of a new strain, potentially a candidate for use in softwoods biopulping processes. Results showed that P. sanguineus was able to reduce lignin content in 11% in 14 days of treatment, but also that P. taeda wood suffered notable structural changes of lignin and hemicelluloses during the treatment, as revealed from 13C CP-MAS NMR spectra. An increase of 15% in porosity of decayed wood confirmed physical changes due to fungal attack. Fil: Levin, Laura Noemí. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Micología y Botánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Micología y Botánica; Argentina Fil: Villalba, Laura. Universidad Nacional de Misiones; Argentina Fil: Da Re, Cristina Verónica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina Fil: Forchiassin, Flavia. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina Fil: Papinutti, Víctor Leandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Micología y Botánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Micología y Botánica; Argentina